The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/aobpla/pls020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the borders of European Phragmites within a cosmopolitan genus

Abstract: European Phragmites australis is one of four main cp-DNA haplotype clusters present worldwide. The European gene pool extends from North America to Far East Asia and South Africa. Extensive gene flow occurs only within the temperate region of Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(144 citation statements)
references
References 38 publications
7
137
0
Order By: Relevance
“…T4c, T4d and T4e are less understood. These LH have been found in southern Europe and North Africa and also pair with R4b (Lambertini et al 2012b;Saltonstall unpublished data). Lambertini et al (2012b) refer to these samples as Haplotypes M3, M4 and M5.…”
Section: Variation Within and Between Haplotypessupporting
confidence: 55%
“…T4c, T4d and T4e are less understood. These LH have been found in southern Europe and North Africa and also pair with R4b (Lambertini et al 2012b;Saltonstall unpublished data). Lambertini et al (2012b) refer to these samples as Haplotypes M3, M4 and M5.…”
Section: Variation Within and Between Haplotypessupporting
confidence: 55%
“…Furthermore, our result revealed that epigenetic structure showed a positive correlation with genetic structure, and epigenetic (as well as genetic) distance also provided coincident evidence for the identified migration of P. australis (Lambertini, Sorrell et al., 2012; Saltonstall, 2002), but epigenetic distance compared with genetic distance was clearly reduced and possibly more related to individual microhabitats. For example, coefficients of genetic differentiation supported the previous haplotype‐based conclusion that P. mauritianus contributed to the hybridization of the LAND type of P. australis (Lambertini, Sorrell et al., 2012), but the epigenetic evidence in our study cannot (Table 3). …”
Section: Discussionmentioning
confidence: 98%
“…In the Gulf Coast region, there may be very strong gene flow within and/or among lineages (Meyerson, Lambertini, McCormick, & Whigham, 2012), which caused a relatively high level of genetic diversity. The LAND and DELTA groups were established by independent colonization events (Lambertini, Sorrell et al., 2012), and the LAND group possessed a higher level of genetic diversity than the DELTA group which suggested introduced DELTA group lost some genetic diversity during the invasion process but obtained little genetic variation through interbreeding with other local lineages. This assumption is also supported by the little genetic and epigenetic differentiation between the DELTA and MED groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations